Offenders with Schizophrenia: Relationship to Psychopathology - Huri, Surina Zaman; Othman, Zahiruddin; Yasin, Mohd Azhar Mohd; Salleh, Rabaiah Mohd (Malaysian Psychiatric Association, 2013)
Objectives: To study the relationship between psychopathology and characteristics of offenders with schizophrenia. Methods: In this cross sectional study, 70 consecutive offenders with schizophrenia (aged 18-65) admitted to Hospital Bahagia Ulu Kinta within a six-month period were studied. Subjects’ psychopathology was assessed using Positive and Negative Syndrome Scale (PANSS). Results: Offenders against person group received treatment at later age (p=0.043) compared to against property and drug or firearm-related offenders groups. Offenders in drug or firearm-related group had significantly higher PANSS negative scores (p=0.015). Unsound mind at the time of offense was significantly associated with high PANSS positive scores (p=0.011) and offenders against person or property groups (p=0.004). Conclusion: Offenders against person had a significantly later age of treatment and probably onset of illness. Unsoundness of mind was significantly associated with positive symptoms and more frequently reported among offenders against person or property. Offenders in drug or firearmrelated group were significantly associated with negative symptoms.